Pilot outcomes from a multidisciplinary telehealth versus in‐person intensive outpatient program for eating disorders during versus before the Covid‐19 pandemic. Issue 9 (10th July 2021) - Levinson, Cheri A.; Spoor, Samantha P.; Keshishian, Ani C.; Pruitt, Alexandria
Abstract: Introduction: Eating disorders (EDs) are serious mental illnesses with high rates of mortality, morbidity, and personal and societal costs. Onset of the Covid‐19 pandemic led to increased ED diagnoses in the general public, as well as worsening of ED symptoms in those with an existing ED diagnosis. Heightened prevalence and severity of EDs during the pandemic is complicated by the fact that traditional modes of ED care (specialty intensive treatment provided by a multidisciplinary team) have been difficult to access during the pandemic. Methods: The current between‐groups study ( N = 93 ED) tested a multidisciplinary intensive outpatient program (IOP) delivered via in‐person (pre‐pandemic; n = 60) and virtually via telehealth (during the pandemic; n = 33). Results: We found no differences in outcomes via delivery mode, such that regardless of in‐person versus telehealth programming, ED symptoms, depression, and perfectionism significantly decreased and body mass index significantly increased. Conclusions: Our findings suggest that a multi‐disciplinary telehealth ED IOP program is feasible and has comparable outcomes to in‐person IOP treatment. These findings have implications for treatment beyond the pandemic, suggesting that adoption of telehealth IOPs is warranted. Such delivery modes of intensive treatments for EDs could be expanded to reach underserved populations, especially in rural areas where treatment is often difficult to access.